“Caracterización morfológica y molecular de agentes patogénicos en plantaciones de gmelina arbórea roxb (melina)” en tres zonas representativas del Ecuador - Tercero Tercero, Holguer (2020)
Melina (Gmelina arborea (Roxb) is a forest species that has characteristics of rapid growth and produces high-quality wood. Currently, there is a reported increase in mortality in this country due to trunk cancer and whose causative agent has been until now unknown. In order to identify the causative agent, samples of 2-year-old symptomatic trees were collected from four Melina producing areas belonging to the company “Company Name” which were identified as Pitzara (CE28), La Palma (CH32A ), Silanche (CJ30A) and Vergel (CH22A). The isolates were carried out in Papa dextrose agar culture medium by sowing fragments taken from the disease progression of approximately 2 cm in an equidistant manner. Pure cultures of a fungus were obtained, which was identified by comparing its micro and macroscopic characteristics with specialized taxonomic keys. Cultural characteristics and microscopic structures coincided for the isolation of the different areas. Fusarium sp. Finding greater similarities with the species F. solani. The isolates were subjected to radial growth tests in PDA medium determining the existence of a significant difference between the strains being the one belonging to the Silanche sector (Rodal CJ30A) which presented the highest growth rate at 2.4 and 7 ddi and thus inferring that This is the most pathogenic strain. In the spore count, the strain with the highest concentration was that belonging to Las Palmas (CH32A) with an average of 2.67 X105. The in vitro antagonistic effect of PGPR Acinetobacter calcoaceticus (PM2-12), Pseudomona protens (CHA0), Serratia marcescens PM3-8, Pseudomona veronii R4, Enterobacter absuriae PM3-14 and the fungus Trichoderma sp. . The trials resulted in the strains belonging to P. protens CHA0 and Trichoderma sp. They presented the highest averages of suppression of radial growth with percentages of 81.68 and 70.08% respectively. In the variable number of spores, it was found that all treatments showed a significant reduction, highlighting treatments consisting of P. protens CHA0 and Trichoderma sp with inhibition rates of 85.6 and 80.86%. determining its potential as biocontrol agents for in vivo tests. DNA from the 4 strains under study were extracted using the Dneasy kit and miniplant kit were collected in eppendorf tubes and the polybarase chain reaction of the enterobacterial repetitive intergenic consensus (ERIC-PCR) was applied for fungal molecular genotyping and thus determine genetic variations intraspecific. Keywords: G. arbórea, vascular wilt, Isolates, fungal isolation, radial growth,Fusarium sp. antagonistic tests PGPR ,Trichoderma sp.